Nutritional Knowledge and Dietary Habits of Student-Athletes in a State University: Towards a Contextualized Nutrition Education Plan - De Jesus, Ma. Jim Rushty M.; Fabian, Leanne N.; Javeluna, Jersey C.; Laquimin, Saycell D.; Cayanan, Criselda Mae D.; Dizon, Stephanie G. (Future Science / FSH-PH Publications, 2023)
Sustainable Development Goal 2 aims to end hunger, achieve food security, improve nutrition, and promote healthy and sustainable diets. Student-athletes deal with unique challenges due to the demands of physical and mental requirements of their sports, making proper nutrition and dietary habits crucial for their overall health and performance. Therefore, this study aimed to analyze the relationship between nutritional knowledge and dietary habits among State Colleges and Universities Athletic Association (SCUAA) Athletes at a state university in Pampanga, Philippines, as a basis for the development of a contextualized Nutrition Education Plan (NEP). The study was grounded on a postpositivist philosophical worldview that employed a quantitative non-experimental approach, specifically a correlational design. A total of 177 student-athletes were assessed for their nutritional knowledge and dietary habits using survey questionnaires. It was determined that student-athletes’ level of nutritional knowledge was described as “knowledgeable” while their perceived dietary habits were described as “good”, but still, there is an area for continued improvement. Meanwhile, it was found that there was no significant difference between nutritional knowledge and dietary habits of student-athletes when grouped according to their demographic profile. On the other hand, there was a significant but weak positive relationship between nutritional knowledge and dietary habits of student-athletes. The results of student-athletes’ nutritional knowledge and dietary habits paved the way for a contextualized NEP anchored on the student-athlete. The study recommends generalizing the NEP and considering the other athletes who also need nutrition and dietary habits improvement.